Lessons learned from 20 years of molecular biological tools in petroleum hydrocarbon remediation. Issue 4 (16th August 2021) - Taggart, Dora M.; Clark, Kate
Abstract: Stakeholders of petroleum hydrocarbon‐contaminated (PHC) sites aim to meet remediation goals cost‐effectively. But contaminated sites are typically complex, and when inefficient remediation strategies are implemented, time and money are wasted. Various strategies can be implemented for site remediation and almost all at some point involve a biological component. Therefore, during site characterization, seeing the complete picture by obtaining multiple lines of evidence—chemistry (concentrations of contaminants and daughter products), geochemistry (redox status, electron acceptors, electron donors), microbiology (species and their genes for catalyzing biodegradation of reactions, i.e., functional genes), and the contaminant degradation ongoing at baseline (stable isotope methods)—is critically important for selecting the best remediation strategy. Additionally, molecular biological evidence is important for monitoring treatment progress and informing decisions to retreat, change treatments, or transition to monitored natural attenuation.